Genetic polymorphism of milk protein in TNB cattle - Boztepe, S; Ermetin, O; Akin, N; Tozluca, A; Dogrul, F (The Indian Journal of Animal Sciences, 2012)
Starch gel electrophoresis method was used to phenotype: casein and milk serum proteins for 110 Turkish Native Black (TNB) cows. Frequencies were; Î±â‚†â‚-casein A 0.000,Î±â‚†â‚-casein B 0.925, Î±â‚†â‚-casein C 0.075;Î² -casein A 0.840, -casein B 0.118,Î²-casein C 0.042;Î²-lactoglobulin A 0.234,Î²-lactoglobulin B 0.766,Î²-casein and Î²-lactoglobulin loci were not in genetic equilibrium. However, the herd was in balance for Î±â‚†â‚-casein. The absence of genetic equilibrium for the 2 loci can be explained by chance as the herd was very small. The effect of migration and selection except for natural selection were weak in this herd.